Effect of Exercise Training on Serum Transaminases in Patients With Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Hong, Feng; Liu, Yubo; Lebaka, Veeranjaneya Reddy; Mohammed, Arifullah; Ye, Weibing; Chen, Biqing; Korivi, Mallikarjuna (Frontiers in Physiology, 2022)
Background/Purpose: Nonalcoholic fatty liver disease (NAFLD) constitutes a spectrum of liver diseases associated with various metabolic disorders. Exercise interventions reportedly manage the clinical outcomes of NAFLD, but their efficacy depends on exercise as well as characteristics of patient. We hypothesized that exercise could alleviate the elevated transaminases level, which may be associated with the characteristics of patients (age/bodyweight/sex) or exercise variables (frequency/intensity/duration). Therefore, we examined the effect of exercise on serum transaminases, and identified the variables influencing transaminases in NAFLD patients. Methods: Article search was conducted using electronic databases (PubMed, Web of Science, EMBASE, ScienceDirect, Google Scholar) until December 2021. Studies that involved examination and comparison of the effect of an exercise intervention on alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in NAFLD/nonalcoholic steatohepatitis patients were included. We calculated pooled effect upon a meta-analysis, determined correlations (between transaminases and characteristics of patients/exercise) by meta-regression, and assessed the influencing variable through subgroup analysis. Results: A total of 18 studies (22 trials) with 1098 NAFLD patients (exercise=568; control=530) were included. The pooled outcomes revealed that exercise intervention significantly decreased both ALT (P=0.004) and AST (P=0.001) levels in NAFLD patients. Meta-regression analysis showed decreased ALT (coef.=1.138, P<0.01) and AST (coef.=0.459, P=0.041) after intervention was correlated with the age of patients. Particularly, patients aged 30–39 years (MD:-25.89 U/L, 95% CI:-36.40 to -15.37, P<0.00001) and 40–49 years (MD:-12.17 U/L, 95% CI:-20.38 to -3.96, P=0.004) represented a substantial decrease in ALT levels. Additionally, the 50–59 years age group tended to have decreased ALT levels (MD:-3.94 U/L, 95% CI:-8.19 to 0.31, P=0.07); however, patients above 60 years did not respond (P=0.92) to exercise intervention. In contrast, exercise-induced AST reduction was found in only the 30–39 years age group (MD:-11.92 U/L, 95% CI:-16.78 to -7.06, P<0.00001) and not in patients under the 40–49 (P=0.19), and 50–59 groups (P=0.12) and above 60 years (P=0.15). Conclusion: Our findings suggest that the ‘age’ of NAFLD patients may be an important variable in improving the levels of serum transaminases, and clinically young patients may have greater benefits from exercise than older patients.